(NnATASKA ROMKI(B: [(NrASSKAZ(B];s (NgLAZA ZEMLI(B: [(NrASSKAZ(B] /s (Nm(B.(Nm(B. (NpRI[WINs - (NpRI[WIN(B, (NmIHAILs ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1984)
(Nw SEDXMOJ TOM sOBRANIQ SO^INENIJ m(B.(Nm(B. (NpRI[WINA WO[LI PROIZWEDENIQ(B, (NSOZDANNYE PISATELEM PO MATERIALAM EGO DNEWNIKOW(B,-"(NnATASKA rOMKI(B" ((NiZ DNEWNIKA OHOTY (B1926-1927) (NI (B"(NgLAZA ZEMLI(B".s
rus
Keywords: (NpOWESTI I RASSKAZYs